ESTUDO DO MICROAMBIENTE TUMORAL EM CARCINOMA EPIDERMOIDE ORAL E OROFARÍNGEO E SUA IMPLICAÇÃO PROGNÓSTICA - Daniel, Camila Batista (2020)
Inflammatory cells can assist important processes of carcinogenesis, such as angiogenesis, invasion and metastasis. It has been shown that systemic inflammation, as well as the presence of tumour-infiltrating inflammation cells, negatively affects the cli